La qualité des données de géomarketing - Frédéric Girault; Jean-Marc Orhan (Cybergeo, 1999)
As it is forbidden to deliver the results of the 1990 census at the enumeration district level, an evaluation pattern has been created by a geomarketing company. Thanks to the real data we have for the city of Rouen, we have measured the quality of this evaluation and we have shown how much the addition of the enumeration districts within a grid strengthens the interest of such a process.